Microstrain and Crystal Orientation Variation within Naked Triple-Cation Mixed Halide Perovskites under Heat, UV, and Visible Light Exposure - Zou, Yuqin; Eichhorn, Johanna; Zhang, Jiyun; Apfelbeck, Fabian A.C.; Yin, Shanshan; Wolz, Lukas; Chen, Chun Chao; Sharp, Ian D.; Müller-Buschbaum, Peter (ACS Energy Letters, 2024)
The instability of perovskite absorbers under various environmental stressors is the most significant obstacle to widespread commercialization of perovskite solar cells. Herein, we study the evolution of crystal structure and microstrain present in naked triple-cation mixed CsMAFA-based perovskite films under heat, UV, and visible light (1 Sun) conditions by grazing-incidence wide-angle X-ray scattering (GIWAXS). We find that the microstrain is gradient distributed along the surface normal of the films, decreasing from the upper surface to regions deeper within the film. Moreover, heat, UV, and visible light treatments do not interfere with the crystalline orientations within annealed polycrystalline films. However, when subjected to heat, the naked perovskite films exhibit a rapid component decomposition, induced by phase separation and ion migration. Conversely, under exposure to UV and 1 Sun light soaking, the naked perovskite films undergo a self-optimization structure evolution during degradation and develop into smoother films with reduced surface potential fluctuations.
CRIS-Team Scopus Importer:2024-01-26